QR Decomposition For Adaptive Filtering Application - Okwonu, Friday Zinzendoff (2011)

(untitled)
This thesis is designed to investigate adaptive filtering problem based on QR decomposition techniques. An adaptive filter is a self modifying digital filter that adjusts its parameters in order to minimize a defined error function. Adaptive algorithm is applied to adapt the coefficient of the used filter to nonstationary process in which the coefficient of the adaptive filter is adapted in order to minimize the error function. Adaptive filtering problem is an adaptive form of least squares problem.